133k views
0 votes
Find a solution to the following system of equations.
-2x + y = -3
-x + 2y = 3

User Shad
by
4.7k points

2 Answers

5 votes

Answer:

Step-by-step explanation: 3+2=5

5

User Beki
by
5.5k points
4 votes

Answer: x=3 y=3

Elimination method.

eliminating x and solving for y.

-2x +y=-3

-x+2y=3

-2(-x+2y=3)

2x -4y = 6

Multiply the second equation by -2 so the x’s cancel out.

-2x+y=-3

2x-4y=6

-2x and 2x cancels out

Add like terms

y-=-6

4y=-3

solve.

-3y = -9

divide by -3 on both sides and

y=3

Plug in 3 for the place of y in either either equation.

-2x+ 3= -3

solve for x.

-2x+ 3= -3

-3 -3

-2x=-6

Divide by -2

x=3

User Kfsone
by
5.9k points